Exploring micronutrients and microbiome synergy: pioneering new paths in cancer therapy - Bhatnagar, Kartik; Jha, Kanupriya; Dalal, Nishu; Patki, Ninad; Gupta, Garima; Kumar, Amit; Kumar, Anil; Chaudhary, Sarika (Frontiers in Immunology, 2024)
The human microbiome is the complex ecosystem consisting of trillions of microorganisms that play a key role in developing the immune system and nutrient metabolism. Alterations in the gut microbiome have been linked to cancer initiation, progression, metastasis, and response to treatment. Accumulating evidence suggests that levels of vitamins and minerals influence the gut environment and may have implications for cancer risk and progression. Bifidobacterium has been reported to reduce the colorectal cancer risk by binding to free iron. Additionally, zinc ions have been shown to activate the immune cells and enhance the effectiveness of immunotherapy. Higher selenium levels have been associated with a reduced risk of several cancers, including colorectal cancer. In contrast, enhanced copper uptake has been implicated in promoting cancer progression, including colon cancer. The interaction between cancer and gut bacteria, as well as dysbiosis impact has been studied in animal models. The interplay between prebiotics, probiotics, synbiotics, postbiotics and gut bacteria in cancer offers the diverse physiological benefits. We also explored the particular probiotic formulations like VSL#3, Prohep, Lactobacillus rhamnosus GG (LGG), etc., for their ability to modulate immune responses and reduce tumor burden in preclinical models. Targeting the gut microbiome through antibiotics, bacteriophage, microbiome transplantation-based therapies will offer a new perspective in cancer research. Hence, to understand this interplay, we outline the importance of micronutrients with an emphasis on the immunomodulatory function of the microbiome and highlight the microbiome’s potential as a target for precision medicine in cancer treatment.